Upper Gastrointestinal Bleeding Secondary to Sodium Polystyrene Sulfonate Use: A Rare Adverse Effect of Commonly Prescribed Treatment - Hamzah Shariff; Shiva Naidoo; Ghazal Ghafari; Hongjie Li; Manisha Devi; Kishore Kumar (Case Reports in Gastrointestinal Medicine)
We report a case of a 62-year-old man who was brought in by emergency medical services after a fall and change in mental status. He was found to have severe hyperkalemia, acute kidney injury, and rhabdomyolysis. The hyperkalemia was treated with sodium polystyrene sulfonate (SPS). During hospitalization, he witnessed having black tarry stools along with a significant drop in hemoglobin. Endoscopic evaluation demonstrated nonbleeding large diffuse gastric ulcers with stigmata of recent bleeding, and ulcer biopsy revealed findings consistent with SPS-induced gastric ulceration. No other source of bleeding was localized, suggesting acute upper gastrointestinal bleeding due to SPS mucosal injury.